Proceedings of the 2007 International Symposium on Low Power Electronics and Design 2007
DOI: 10.1145/1283780.1283803
|View full text |Cite
|
Sign up to set email alerts
|

Timing-driven row-based power gating

Abstract: In this paper we focus on leakage reduction through automatic insertion of sleep transistors using a row-based granularity. In particular, we tackle here the two main issues involved in this methodology: (i) Clustering and (ii) the interfacing of power-gated and non power-gated regions within the same block. The clustering algorithm automatically selects an optimal subset of rows that can be power-gated with a tightly controlled delay overhead. We then address the issue of interfacing different gated regions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…To quantify the FoMs of power-gating, we adopted a flow based on the row-based methodology of [5]. The methodology realistically assumes that one or more rows are dedicated to the insertion of the sleep transistors and are appended at the end of the existing layout.…”
Section: Power-gating Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…To quantify the FoMs of power-gating, we adopted a flow based on the row-based methodology of [5]. The methodology realistically assumes that one or more rows are dedicated to the insertion of the sleep transistors and are appended at the end of the existing layout.…”
Section: Power-gating Flowmentioning
confidence: 99%
“…1.1 Clustering and Sizing: As discussed in [5], the clustering algorithm is based on using rows of the layout as atomic clustering objects. It takes two input parameters, namely, the performance (α) and the area (W sleep ) constraints.…”
Section: Power-gating Flowmentioning
confidence: 99%
“…This prevents invalid output voltages during the idle state to be fed to the inputs of nonpower-gated cells, avoiding undesirable side-effects such as short-circuit currents and invalid latching. Alternatively, a pull-up pMOS can be inserted on the virtual ground [4], as shown in Figure 7. After the sleep transistor is turned-off, the pull-up rapidly charges the virtual ground rail to vdd, thus forcing a HIGH logic value to the output of all the connected cells.…”
Section: Reactivation Time Modelingmentioning
confidence: 99%
“…Several embodiments of power-gating do exist. Main differentiation factors include: granularity at which the sleep devices are inserted; methods for sleep transistor sizing under timing/area constraints; physical device implementation (see, for instance, [1]- [4]). One important concern in practical power-gating is the control of the transient currents associated to the transition between the stand-by and the active state (i.e., reactivation or turn-on or wake-up).…”
Section: Introductionmentioning
confidence: 99%
“…In [1] authors propose to separate timing critical standard cells from the non-critical ones by placing them in different rows and by doing the power gating only for the non-critical standard cell rows. They have shown that a high leakage saving can be achieved while losing a small amount of performance.…”
Section: Introductionmentioning
confidence: 99%